Pengaruh Tipe Kepribadian dan Religiusitas Terhadap Subjective Well Being Pada Wanita Yang Berperan Ganda di Jakarta - Chintya Eka Dewi; Ima Sri Rahmani (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2015)
The aim of this study is to determine the predictor variable for subjective well being as dependent variable of woman with multiple roles. Two independent variables, namely personalitiy and religiousity, are used in order to determine which one of these two independent variables would be the best predictor for „subjective well being.‟ As a quantitative research, the multiple regression analysis is used to measure 200 respondents working at some companies located in North Jakarta and Central Jakarta. Scale measurement is modified from the original scale constructed by Diener et.al (1985) for Subjective Well Being Scale, Watson et.al (1988) for Personality Scale and Lewis Goldberg (1992), Fetzer Institute (1999) for Religiousity for our own research. There is a significant influence that personality and religiousity could be a predictif factor to measure „a subjective well being‟ of woman with multiple role. Dimension measured for the variable of personality here are agreebleness, conscientiousness, and openess to experience, while for religiousity: private religious practice, religious/spiritual history, and organizational religiousness.